Desiccation survival time for eggs of a widespread and invasive Australian mosquito species, Aedes (Finlaya) notoscriptus (Skuse). Issue 1 (June 2016) - Faull, K.J.; Webb, C.; Williams, C.R.
ABSTRACT: The Australian native mosquito Aedes ( Finlaya ) notoscriptus (Skuse) is closely associated with natural and artificial water holding receptacles. Eggs are laid in habitats where they are exposed to drying conditions as water levels fluctuate. Withstanding desiccation enables survival in challenging environments and increases the potential for establishment in non‐native habitats. Until now, the desiccation resistance of Ae. notoscriptus eggs has been unknown despite the historical invasive success of this important dog heartworm and arbovirus vector. Viability and mean survival times of eggs from two Ae. notoscriptus populations (metropolitan areas of Sydney, NSW and Adelaide, SA) were evaluated, with eggs stored under three dryness conditions for up to 367 days. Our results revealed that Ae. notoscriptus eggs can withstand desiccation for extended periods, under a variety of conditions, with approximately 9‐13% egg viability recorded after one year. This prolonged egg survival reflects the widespread distribution of this mosquito in Australia and its history of incursions and subsequent establishment in non‐native habitats. Differences in mean egg volume were recorded in addition to significantly different egg length to width ratios for the two populations, which may reflect adaptation to biotope of origin and an associated likelihood of drought and drying conditions. The results of this study suggest that the desiccation resistant eggs of Ae. notoscriptus make this species highly adaptable, increasing the risk of movement to non‐endemic regions of the world.